RIBA DALAM FIAT MONEY PERSPEKTIF SYEIKH ALI JUM’AH DAN SYEIKH IMRON NAZAR HOUSEN - Syarifuddin, Moh.; Awal Amarudin, Amin; Ashlihah, Ashlihah (Universitas KH. A. Wahab Hasbullah, 2025)
Fiat money is a trigger for global economic instability. This has often happened since the Bretton Woods System was inaugurated on a global scale, namely legalizing the practice of printing paper money without any underlying. This research aims to determine the development of fiat money from an economic perspective and to determine the legal status of the use of fiat money according to the perspective of Ali Jum'ah and Imron Housen. This research is a type of Mix Method research by combining Library Research (Library) and Media Research (Social Media Research). The data collection method was obtained through primary data including literature sourced from statutory regulations, books, official documents, publications, research results, and secondary data including social media such as YouTube, Instagram, etc. Data analysis uses Comparative Descriptive Qualitative Analysis to compare the opinions of Ali Jum'ah and Imron Housen. The research results show that the development of fiat money has begun since the issuance of the fatwa on halal bank interest in 1904 by the Mufti of Egypt, Muhammad Abduh, the fatwa on halal paper money in 1984 in Haramain, the establishment of the Federal Reserve in 1913 and then the collapse of the Bretton Woods System in 1971 until now. Ali Jum'ah believes that fiat money is not usury for reasons of 'urf and the maslahah element in the modern era, while Imron Housen says that fiat money is usury on the grounds that fiat money has no intrinsic value. According to him, interest is the main characteristic of the current global financial system, capitalism or neoliberalism (banks, interest and fiat money). Fiat money is the essence of usury, from an Islamic perspective fiat money contains two types of usury at once, namely usury Al Fadl and usury an Nasiah.